Variation in food web reliance on green and brown energy pathways across ecosystem gradients - James W. Sturges; W. Ryan James; Ryan J. Rezek; Rolando O. Santos; Mack White; Gina A. Badlowski; Shakira Trabelsi; Jordan Massie; Justin S. Lesser; Joel C. Trexler; James Nelson; Jennifer S. Rehage (PLoS ONE, 2026)
Aquatic food webs typically include highly coupled fast, ‘green’ energy pathways driven by algae or phytoplankton and slower, ‘brown’ energy channels driven by detritus and terrestrial plants. Quantifying how much energy biological communities obtain from each of these pathways is essential, particularly across multiple interconnected food webs over large areas, because energy dynamics are known to influence ecosystem structure and function. Despite their importance, few studies track variance in energy channel contributions to food webs across interconnected habitats during distinct hydrologic seasons. In this study, we used tri-isotope Bayesian mixing models to quantify seasonal contributions of energy pathways to consumers in nine aquatic food webs across two river drainages in the Florida coastal Everglades. Sites span an ecosystem gradient from freshwater marshes to estuarine riverine mangroves and marine seagrass habitats. We found that green energy channels were the dominant pathway for consumers in 12 of 18 seasonal food webs, with the remaining 6 being more reliant on detrital energy channels. There were contrasting spatiotemporal trends between river networks. Shark River Slough food webs showed a clearer pattern of greener marsh food webs upstream switching to browner food webs more heavily reliant on mangrove detritus downstream. In contrast, Taylor Slough food webs showed the opposite pattern of browner marsh food webs upstream switching to greener food webs downriver and in marine seagrass habitats. Seasonal switching of the dominant energy channel was less common than expected, with 2 of 9 food webs shifting from green to brown dominance between the dry and wet season. Seasonal shifts disrupted spatial gradients in energy channel use, but the seasonal dynamics quantified in this single year study require further contextualization. Our findings provide a short but dynamic view of energy pathways in aquatic communities across the Everglades, but continued research will allow us to better predict how species, food webs, and ecological networks may respond to environmental drivers under future global change.